Perspectives on race in organizations - King, Eden; Roberson, Quinetta M.; Hebl, Michelle R. (Emerald Publishing Limited : Information Age Publishing, Inc., 2023)
"The current volume in the series, focuses on race and racism in organizations. Seventeen experts and trailblazers for building a science around race at work respond to prompts that align with the volume's goal of building understanding and kindling new directions. These giants on whose shoulders new scholarship stands describe their paths to this area of work and the products of which they are most proud before sharing advice and inspiration for scholars and research in the future. Together, these reflections represent poignant examples of why scholarship on race continues to be of critical importance to management science"-- Provided by publisher.
Keywords: Diversity in the workplace.; Racism in the workplace.; Business & Economics -- Diversity & Inclusion.; Diversity, equality and inclusion in the workplace.; elektronické knihy; electronic books